P3.100 Filling the Knowledge Gap: Measuring HIV Prevalence and Risk Factors Among Populations Most Vulnerable to HIV in Libya. (13th July 2013) - Valadez, J J; Berendes, S; Jeffery, C; Thomson, J; Othman, H Ben; Moxon, S; Danon, L; Turki, A A; Saffialden, R; Mirzoyan, L
Abstract : Background: There has been no sound evidence on the status and dynamics of Libya's HIV-epidemic, which is urgently needed to inform near-term policy making while the window of opportunity to act is still open. With funding from the European Union we therefore aimed to assess HIV prevalence and related risk factors among populations most vulnerable to HIV. Methods: Using respondent-driven sampling, we conducted a cross-sectional survey among 328 people who inject drugs (PWID), 227 men having sex with men (MSM), and 69 female sex workers (FSW) in Tripoli. We collected behavioural data and blood samples for HIV, hepatitis C and B testing. Results: We estimated HIV-prevalence of 87% among PWID, 3% among MSM, and 16% among FSW. We detected high levels of IDU-related, and sexual risk factors, in the context of strong stigma and lack of prevention programmes. Of particular concern, 85% of PWID reported having shared needles, only 21% of MSM used a condom at last sex, and 28% of FSW experienced STI symptoms during the last year. Over a third of MSM had risky sex with men and women and nearly a third of FSW had 50 or more sexual partners in the past six months. Conclusion: In this first bio-behavioural survey in Libya we detected among PWID one of the highest (or even the highest) levels of HIV-infection worldwide in the absence of a comprehensive harm-reduction programme. There is urgent need to implement an effective National HIV-Strategy informed by the results of this research, and designed to account for the overlap of high-risk sexual and drug-using networks. The risk of further transmission within different risk groups and to the general population is particularly high given the recent military events that led to increased violence, migration, and the disruption of essential HIV-related services and structures.